Human Resource Management in Improving The Quality Of Teachers in Indonesian Islamic Primary Education Institutions - Makherus Sholeh; Raihanatul Jannah; Khairunnisa; Nur Kholis; Ghada Tosson (Study Program of Education for Islamic Elementary School Teachers (Undergraduate), Faculty of Tarbiyah and Education (FITK), Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
Human Resource Management (HRM) problems are familiar at all educational institutions, such as the Islamic Basic Educational Institution. This study aims to reveal and introduce the concept of HRM in improving the quality of teachers at the SDI (islamic elementary school) Qurrota A'yu Tulungagung, Indonesia, to show the importance of HR in improving the quality of teachers in Islamic Primary Educational Institutions. Furthermore, this research involves ten informants, including a school principal, teachers, committees, parents, and community leaders. Subsequently, data were collected through in-person interviews (via telephone and online by WhatsApp messaging services), participant observation, and documentation. The results show the process of human resource management in improving the quality of teachers through planning, training, and evaluation. Firstly, the planning strategy is conducted through preservice education or recruitment, while the training strategy is conducted by making on-the-job and offthe-job training programs. Lastly, Every week, semester, and year, the evaluation is completed, and rewards are given. In conclusion, the findings imply that human resource management has an important role in determining the quality of teachers.